A study on methods for detection in clandestine methamphetamine laboratories - Khai, Lee (2021)
Methamphetamine-related problems appear to threaten globally, and over one third of the estimated global number of users was recorded in East and South-East Asia. This is a serious security and health issue, as well as the potential hazards arisen from clandestine methamphetamine laboratories, considering many of such laboratories which are not detected. From forensic science perspective, quick determination of illicit products and related activities in a discovered clandestine laboratory is crucial. From the public’s perspective, a structure, particular residential structure, must be determined whether it is safe from exposure of methamphetamine residues after dismantlement and remediation. Therefore, this study was aimed to establish a series of strategies for methamphetamine detection potentially applicable in the varying settings of clandestine laboratory situations. In this study, colour tests, digital image analysis, ultraviolet-visible (UV-Vis) spectrometry, gas chromatographic techniques, and electrochemical detection were investigated. Subsequently, the percentage recoveries of residual surface methamphetamine from the common household surfaces were determined. The results show that Marquis and Simon’s test allowed detection down to 5 μg and 10 μg of methamphetamine, respectively. Aiding by digital image analysis, the Yellow and Cyan intensities were successfully applied to objectively interpret the Marquis and Simon’s test, allowing detection at 1 μg and 10 μg, respectively. UV-Vis spectroscopy detected methamphetamine at wavelength of 469 nm for Marquis test and 580 nm for Simon’s test with respective detection limits at 1.0 μg/mL and 2.5 μg/mL. Subsequently, gas chromatography analysis on trifluoroacetic acid anhydride derivatised methamphetamine had increased the sensitivity, enabling positive detection in a linear range from 19.53 ng/mL to 2.5 μg/mL and achieving detection limit of 2.44 ng/mL. Residual methamphetamine level at 0.5 μg/100 cm2 were successfully detected on four different surfaces, where good recoveries were achieved on glass (62.49%), plastic (69.47%) and stainless-steel surfaces (72.66%), while relatively lower recovery was reported on unvarnished woof surfaces (33.78%). Electrochemical detection technique using glassy carbon electrode modified with graphene oxide was able to detect methamphetamine as low as 0.041 μg/mL. To conclude, a framework of methamphetamine detection strategies was established and readily applied to different scenarios of clandestine methamphetamine laboratories based on their respective sensitivities as well as the availability and type of samples to be recovered. A novel electrochemical detection upon electrode modification was also developed and established. This study would be beneficial to assist forensic investigation and to ensure the safety of occupants, thus promoting a better societal well-being.